Understanding how virtual reality forest experience promote physiological and psychological health for patients undergoing hemodialysis - Hsieh, Chung-Heng; Li, Dongying (Frontiers in Psychiatry, 2022)
Growing research has found that exposing patients to forest landscapes through technology improves their health. However, studies on the effects of nature therapy sessions on particularly vulnerable groups that require frequent regular treatment such as patients of chronic kidney disease is lacking. This study aims to understand the effects of watching panoramic videos of forest walks through virtual reality (VR) headsets on patients. We also examine the effects of the frequency of virtual exposure to forests on the physiological and psychological parameters of patients undergoing dialysis. Twenty-four dialysis patients with a mean age of 65.11 year underwent a virtual nature intervention over the course of 3 weeks. The intervention consists of 3 numbers of 6-minute 360-degree nature videos delivered using VR headsets. We measured heart rate variability and heart rate using continuous electrocardiographic (ECG) monitoring and assessed their emotional states using a questionnaire survey and in-depth interviews. The results showed that the initial 6 minutes of watching of the panoramic videos through VR headsets resulted in significantly reduced heart rate and sympathetic nerve activity and increased positive emotional responses. However, repeated VR exposure did not further improve the physiological health of the respondents. Considering these results, the use of VR headsets to watch 6-minute nature videos indoors can be used to enhance the positive psychological responses among dialysis and bed-ridden patients. As this study is preliminary, future random controlled trials are needed to compare and determine the best dose, content, and delivery methods of such an intervention.